2018
DOI: 10.1007/s11524-018-0268-0
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Sleep Problems by Sexual Orientation among New York City Adults: an Analysis of the New York City Health and Nutrition Examination Survey, 2013–2014

Abstract: We examined disparities in sleep problems by sexual orientation among a population-based sample of adults, using data from the New York City (NYC) Health and Nutrition Examination Survey (NYC HANES), a population-based, cross-sectional survey conducted in 2013-2014 (n = 1220). Two log binomial regression models were created to assess the relative prevalence of sleep problems by sexual orientation. In model 1, heterosexual adults served as the reference category, controlling for gender, age, race/ethnicity, edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
1
10
2
Order By: Relevance
“…This finding adds additional supports to the previous findings that healthy sleep habits and environment can possibly serve as a buffer against poor sleep quality (Brown et al, 2006;Sato & Ambo, 2018). It is also worth noting that while the current study discovered a significant relationship between sleep quality and age, sleep quality was not associated with other sociodemographic variables (i.e., sex, race, and annual household income), a finding which was inconsistent with the previous studies (Arber et al, 2009;Duncan et al, 2018;Fuller-Rowell et al, 2017;Sivertsen et al, 2017).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This finding adds additional supports to the previous findings that healthy sleep habits and environment can possibly serve as a buffer against poor sleep quality (Brown et al, 2006;Sato & Ambo, 2018). It is also worth noting that while the current study discovered a significant relationship between sleep quality and age, sleep quality was not associated with other sociodemographic variables (i.e., sex, race, and annual household income), a finding which was inconsistent with the previous studies (Arber et al, 2009;Duncan et al, 2018;Fuller-Rowell et al, 2017;Sivertsen et al, 2017).…”
Section: Discussioncontrasting
confidence: 55%
“…There are two age subgroups: (1) the younger group (aged 30 or below 30 years); (2) the older group (aged over 30 years). Race/ethnicity, sex, and annual household income were also included as control variables in the multiple regression models since the prior research has documented significant differences in sleep quality according to race/ethnicity (Fuller-Rowell et al, 2017), sex (Arber et al, 2009;Duncan et al, 2018), and low household income (Sivertsen et al, 2017). Tolerance value of each predictor indicated that there was no sign of multicollinearity.…”
Section: Multiple Regression Analysesmentioning
confidence: 99%
“…11 Data from the 2013-2014 New York City Health and Nutrition Examination Survey indicated that bisexual adults were at higher risk for sleep problems than heterosexual adults. 12 Data from Wave IV of the National Longitudinal Study of Adolescent to Adult Life indicated that sexual minority adults have greater trouble falling and staying asleep than heterosexual adults. 13 Despite the aforementioned studies, which point to the presence of sexual orientation disparities in sleep behaviors among adults, the literature on sexual orientation and sleep behaviors among adolescents is almost nonexistent.…”
Section: Sexual Orientation and Sleep Behaviorsmentioning
confidence: 99%
“…That can make me more-I feel like my body is more visible. (Transgender male and non-binary, gay/lesbian, and queer, White, age 19) Furthermore, six participants (15%) specifically discussed how their own gender self-identification, perception by society, and physical presentation impacted their sleep quality:…”
Section: Mental Healthmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] Moreover, a growing body of empirical research has demonstrated that poor sleep health is disproportionately experienced by sexual and gender minority populations. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Increasingly, studies have focused on sleep among lesbian, gay, and bisexual (LGB) individuals, showing similar associations with adverse health outcomes. 16,18,19,25,27 While evidence also strongly suggests that difficulties falling and remaining asleep may be risk factors for poor mental health, substance abuse, and sexual risk behaviors, most studies to-date have focused on gay, bisexual, and other men who have sex with men (MSM) 18,25,27,28 with very little research conducted among other sexual minority groups and gender minority groups.…”
Section: Introductionmentioning
confidence: 99%